2019
DOI: 10.1016/j.jeem.2018.11.008
|View full text |Cite
|
Sign up to set email alerts
|

Conservation agriculture and climate resilience

Abstract: Agricultural productivity growth is vital for economic and food security outcomes which are threatened by climate change. In response, governments and development agencies are encouraging the adoption of ‘climate-smart’ agricultural technologies, such as conservation agriculture (CA). However, there is little rigorous evidence that demonstrates the effect of CA on production or climate resilience, and what evidence exists is hampered by selection bias. Using panel data from Zimbabwe, we test how CA performs du… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
78
0
5

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 155 publications
(89 citation statements)
references
References 59 publications
6
78
0
5
Order By: Relevance
“…Although widely considered one of the most appropriate climatesmart agricultural technologies for smallholder farmers in sub-Saharan Africa (e.g., African Conservation Tillage Network, 2016;Michler, Baylis, Arends-Kuenning, & Mazvimavi, 2016), smallholder implementation of CA is often short-lived. Evidence from literature and practice points to a growing problem of dis-adoption (Andersson & Giller, 2012;Arslan, McCarthy, Lipper, Asfaw, & Cattaneo, 2014;Twomlow & Delve, 2016).…”
mentioning
confidence: 99%
“…Although widely considered one of the most appropriate climatesmart agricultural technologies for smallholder farmers in sub-Saharan Africa (e.g., African Conservation Tillage Network, 2016;Michler, Baylis, Arends-Kuenning, & Mazvimavi, 2016), smallholder implementation of CA is often short-lived. Evidence from literature and practice points to a growing problem of dis-adoption (Andersson & Giller, 2012;Arslan, McCarthy, Lipper, Asfaw, & Cattaneo, 2014;Twomlow & Delve, 2016).…”
mentioning
confidence: 99%
“…Under these climate conditions with drought severity, increase in irrigation practices could also be a strong contributing factor for the increase in harvested acreage 10. While a meta‐study by Ogle et al reported no changes in productivity with no‐till in wet and/or cool areas,13 long‐term studies revealed that CA was beneficial only in dry years and areas 3,14. Accordingly, to increase harvested cropland in semi‐arid conditions such as Arizona (Figure 2 and Table 1), sustainable on‐farm CA practices such as no‐till, reduced tillage, and cover cropping (Figure 3) are required.…”
Section: Discussionmentioning
confidence: 99%
“…Na agricultura, a variabilidade da produção é afetada em até 80% pelas condições meteorológicas. A precipitação pluviométrica é o elemento mais importante e o atributo climático de maior expressão e significância nas regiões de clima tropical e subtropical, onde a sua distribuição variável anualmente e períodos de chuva extrema e seca influenciam nas diversas atividades humanas (AYOADE, 1986;PELL et al, 2007;CARAMORI et al, 2008;AGOVINO et al, 2018;GELCER et al, 2018;MICHLER et al, 2018).…”
Section: Introductionunclassified